2013
DOI: 10.1155/2013/291592
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy ofPlectranthus amboinicus(Lour.) Spreng in a Murine Model of Methicillin-ResistantStaphylococcus aureusSkin Abscesses

Abstract: The present work aimed to evaluate the effectiveness of Plectranthus amboinicus (Lour.) Spreng against MRSA clinical isolates. The in vitro antimicrobial activity of the hydroalcoholic extract (HE), the ethyl acetate (EA) fraction and its subfractions were determined by broth microdilution and bioautography against MRSA clinical isolates. The microdilution checkerboard method was used to assess in vitro drug combination studies. To induce abscess formation, bacterial suspensions were added to Citodex and inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…However, the last decade witnessed a large increase of scientific interest in P. amboinicus research, as evidenced by increasing numbers of publications related to the bioactivities of P. amboinicus. This plant extract exhibited antibacterial activity against methicillinresistant Staphylococus aureus in a murine model [4], and was proven effective against reproductive tract infections by Candida albicans, Proteus vulgaris and Klebsiella pneumoniae [5]. It has been reported that P. amboinicus possesses anti-inflammatory and antitumor activities [6], larvicidal [7], and antithrombotic and antioxidant activities [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the last decade witnessed a large increase of scientific interest in P. amboinicus research, as evidenced by increasing numbers of publications related to the bioactivities of P. amboinicus. This plant extract exhibited antibacterial activity against methicillinresistant Staphylococus aureus in a murine model [4], and was proven effective against reproductive tract infections by Candida albicans, Proteus vulgaris and Klebsiella pneumoniae [5]. It has been reported that P. amboinicus possesses anti-inflammatory and antitumor activities [6], larvicidal [7], and antithrombotic and antioxidant activities [8].…”
Section: Introductionmentioning
confidence: 99%
“…amboinicus . This plant extract exhibited antibacterial activity against methicillin-resistant Staphylococus aureus in a murine model [ 4 ], and was proven effective against reproductive tract infections by Candida albicans , Proteus vulgaris and Klebsiella pneumoniae [ 5 ]. It has been reported that P .…”
Section: Introductionmentioning
confidence: 99%
“…Various compounds from medicinal plants can be used to treat and prevent infections, and enhance immune function [6] , [7] . However, only a few medicinal plant extracts have been shown to assist the host immune system to overcome infection with antibiotic-resistant strains of S. aureus [8] , [9] . Rhodomyrtone, a bioactive compound from the leaves of Rhodomyrtus tomentosa , has pronounced antibacterial activity against several Gram-positive bacteria, including S. aureus and MRSA [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative measurement of MIC values indicates that the extracellular extract has higher antibacterial activity compared to intracellular extract (p < 0.05). The ability of extracellular pigment extract of P. rubra BF1A IBRL to inhibit S. aureus and S. aureus (MRSA) to a greatest extent is an advantage because of the alarming resistance of the strain towards many antibiotics, which caused by the occurrence of mecA gene (gene that encodes resistance to methycillin) in the DNA of MRSA strain (De Olivera et al, 2013).…”
Section: Description Characterization and Identification Of The Marimentioning
confidence: 99%